Overcoming beta-lactam resistance in Pseudomonas aeruginosa by targeting metallo-beta-lactamase VIM-1: a one-microsecond molecular dynamics simulation study - Mohammed Salleh M. Ardawi; Samar A. Badreddine; Muhammad Yasir; Muhammad Yasir; Aiah M. Khateb; Aiah M. Khateb; Safaa A. Turkistani; Ahmed Afandi; Samah O. Noor; Adhari Alselmi; Adhari Alselmi; Vivek Dhar Dwivedi; et al. (Frontiers in Cellular and Infection Microbiology)
Pseudomonas aeruginosa (P. aeruginosa) is a Gram-negative opportunistic pathogen with a high resistance to beta-lactam antibiotics, mainly due to the production of metallo-beta-lactamase VIM-1 (MBL-VIM-1) enzyme. This study aimed to identify new inhibitors targeting MBL-VIM-1 to restore the efficacy of beta-lactam antibiotics. Extensive screening of natural compounds from the COCONUT database was performed to identify the structural analogs of the existing inhibitor of the MBL-VIM-1 protein. The virtual screening process selected four top-performing compounds (CNP0390322, CNP03905695, CNP0079056, and CNP0338283) that exhibited promising docking scores. These compounds were then subjected to re-docking and one-microsecond molecular dynamics (MD) simulations to assess their binding stability and interactions within the MBL-VIM-1 active site. Finally, post-MD simulation calculations were employed to estimate the interaction strengths and compare the efficacy of these compounds against the reference inhibitor. The findings highlighted that these four potent MBL-VIM-1 inhibitors show superior binding affinity and stability, suggesting their potential to combat antibiotic resistance in P. aeruginosa. The identified compounds offer a promising avenue for developing novel therapeutics to restore the efficacy of beta-lactam antibiotics against resistant bacterial strains. Therefore, further in vitro and in vivo studies are warranted to validate their potential.